Annotated checklist of aphyllophoroid fungi of Ukraine - Akulov, A. Yu.; Usichenko, A. S.; Leontyev, D. V.; Yurchenko, E. O.; Prydiuk, M. P.; Акулов, Олександр Юрійович; Усіченко, Андрій Сергійович; Леонтьєв, Дмитро Вікторович; Юрченко, Євген Олегович; Придюк, Микола Павлович (My University, 2003)
The checklist of aphyllophoroid fungi (except of taxa with typical clavarioid and stipitate cantharelloid basidiomata) based on the data of literature since 1842 and examined collections from WU, KW, LE, and MSK herbaria includes 461 species. Five species are belonged to doubtful records; 30 names are classified as dubious, confused, or of unclear application. The species are accompanied with the numbers of reference herbarium specimens, data on the earliest publishing for Ukraine, distribution in botanic- geographical districts (geobotanical regions) of Ukraine, and appropriate numbered literature references. Besides of upto-date nomenclature, the synonyms used in the quoted publications and herbarium labels are listed. Six species are recorded from Ukraine for the first time on the base of collections gathered by the authors. The new species and new finds for the geobotanical region (districts) are provided by brief information about locality, substratum, collector(s), and date of collection. Taxa are arranged according to the system accepted in the 9th edition of Ainsworth and Bisby's dictionary of the fungi . The checklist is supplemented by the floristic bibliography on aphyllophoroid fungi of Ukraine with titles in original languages and in English.
Анотований список афілофороїдних грибів України
Keywords: NATURAL SCIENCES::Biology::Organism biology::Plant physiology; Aphyllophorales; biodiversity; history of investigation; distribution; nomenclature; Ukraine